SYSTEMATIC LITERATURE REVIEW (SLR): THE IMPORTANCE OF FLEXIBILITY AND ORGANIZATIONAL CULTURE FOR SMES TO SURVIVE IN A HIGHLY COMPETITIVE MARKET - Auliya Az Zahra; Yani Dwi Restanti; A. Faiz Fadl.Lulloh (RADJA PUBLIKA, 2026)
Operational flexibility is a critical factor enabling SMEs to adapt to market changes. This study aims to analyze how operational flexibility supports SMEs in navigating market dynamics while enhancing business efficiency, as well as to examine how the synergy between an adaptive organizational culture and operational flexibility can create a competitive advantage for SMEs. The method used is a Systematic Literature Review (SLR) of 18 sources selected based on quality and relevance criteria. The results show that operational flexibility enables SMEs to respond quickly to market changes through resource optimization and strategic decision-making, while improving efficiency through the application of innovative technologies and the adjustment of business strategies to market needs. Furthermore, the synergy between operational flexibility and an adaptive organizational culture characterized by the values of collaboration, innovation, and learning forms dynamic capabilities that strengthen SMEs’ competitiveness. This study contributes by broadening our understanding of the strategic role of operational flexibility and an adaptive organizational culture in enhancing SME performance, and recommends integrating both as a comprehensive approach to strengthening competitive advantage amid increasingly complex market competition.